System for analyzing medical data / Saravanabavan Ramasamy - Saravanabavan, Ramasamy (2002)
This project can be defined as a stand-alone system, which attempts to integrate with Healthcare Information System to communicate the outside and inside flow of information in hospitals and provide the functions common for all applications. This web-based Medical Data Analysis System allows all range of users, using Internet Explorer web browser to view the graphical output from the patient's data and gaining mild information about the top ten diseases ranked in Malaysia or specifically University Malaya Medical Center. On the other hand, it allows the authorized user to update the latest patent medical data and diseases name as time change . The rational behind this development is to give comparison in several aspect such as sex , race, state, height, weight, occupations and age. A combination of waterfall model and prototyping model was selected for the development process because it supports rapid application development and reduce the risk involved. Software engineering principles based on this methodology were applied throughout the whole development phase of the system such as system analysis, implementation design testing and coding. The development tools selected for this project were Microsoft Visual Basic 6.0, Intercooled Stata SOftware 6.0 and ACD See. The patient's data are kept in stata's Data Editor and Internet Information Server is used as the web server. Microsoft Windows 2000 has been chosen as the operating system where it is known for it's powerful platform for web application development and deployment.